2010
DOI: 10.1038/jhh.2009.109
|View full text |Cite
|
Sign up to set email alerts
|

Switching of antihypertensive drugs among 93 286 Chinese patients: a cohort study

Abstract: Antihypertensive drug switching induces substantial public health costs. This cohort study evaluated factors associated with switching of antihypertensive agents 180 days after the first date of prescription among ethnic Chinese patients. We included all adult patients aged > or =18 years, who had paid at least two consecutive visits to all public primary care clinics in one large territory of Hong Kong during the study period from January 2004 to June 2007. Binary logistic regression analyses were carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This study also allowed the analysis of a considerable number of factors associated with antihypertensive drug changes. Further, several studies that assessed changes in antihypertensive drug treatment used only two [1,26,27] or three categories such as “continuers”, “switchers” and “discontinuers” [14]. In this study, we opted for a four-category classification as suggested by Mazzaglia and colleagues [7] because it reflected more accurately the behavior of a practitioner when managing a patient with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…This study also allowed the analysis of a considerable number of factors associated with antihypertensive drug changes. Further, several studies that assessed changes in antihypertensive drug treatment used only two [1,26,27] or three categories such as “continuers”, “switchers” and “discontinuers” [14]. In this study, we opted for a four-category classification as suggested by Mazzaglia and colleagues [7] because it reflected more accurately the behavior of a practitioner when managing a patient with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent evaluation of adherence profiles of antihypertensive agents in Chinese, we reported that hypertensive patients were consistently more likely to be adherent among the older patients and follow-up visitors but there were conflicting results about adherence in men and women. [15][16][17][18][19][20][21][22] Nevertheless, these studies measured the adherence profiles to antihypertensive agents only, and little was known about adherence patterns to oral hypoglycemic agents (OHAs) in ethnic Chinese.…”
mentioning
confidence: 99%
“…Unlike the study conducted in the Chinese population, where combination therapy (single pill combination) showed less likelihood of drug switching, our study showed that the polytherapy was significantly associated with a change in the medication. [ 14 ] However, polytherapy could be a single pill combination or multiple pill combination which was not differentiated in our study; this multiple pill combination could have led to antihypertensive medicine switchover as >1 drug/multiple pill combination used for treating HTN may prime to inefficient BP control due to less adherence. [ 21 ] In addition, it was also seen that increasing the number of pills had a negative effect on compliance and on persistence on therapy, translating into poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 91%
“…[ 17 18 ] On the other hand, studies from China disclosed very less switchover (5.7% and 3.9%) of antihypertensive medication. [ 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation